Initial ball flight characteristics of curve and instep kicks in elite women`s football - Alcock, A.; Gilleard, W.; Brown, N. A. T.; Baker, J.; Hunter, A. (Journal of Applied Biomechanics, 2012)
Initial ball flight characteristics of curve and instep kicks were investigated. Fifteen international female footballers performed curve and instep kicks from a distance of 20 m from goal and at a 1 m2 target. Seventeen Vicon cameras tracked three-dimensional coordinates of four reflective markers adhered to the ball. Ball flight characteristics were quantified, and the coordinates of the ball relative to the target center were recorded. The lateral launch angle and the angle of the spin axis relative to the horizontal best predicted the horizontal placement of the ball relative to the target. The vertical launch angle, antero-posterior velocity and amount of backspin best predicted the vertical coordinate. Regression models demonstrated how carefully controlled the flight characteristics must be with launch angles constrained within 3° to hit the target. Curve kicks were characterized by significantly greater lateral and vertical launch angles, increased sidespin and spin about the antero-posterior axis, and a more vertical spin axis. This information is beneficial for coaches in training players to achieve the characteristics required to score a goal and avoid a defensive wall. For example, if players consistently kick above or below the target, these findings identify the variables that will help rectify that error.